REPRESENTASI DAKWAH KEPADA GENERASI MILENIAL: Analisis Semiotika Roland Barthes Dalam Film Ustadz Milenial - Christin Nur Aisyah; Asna Istya Marwantika (Institut Agama Islam Negeri (IAIN) Ponorogo, 2023)
Abstract: Film is not only a medium of entertainment but can be developed as a medium of delivering da'wah. Ustadz Millennial Film is one of them, which represents Islamic messages or da'wah. This study uses Roland Barthes' semiotic analysis approach to reveal the meaning of denotations, connotations, myths, and the message of da'wah in the film. This research uses a qualitative approach with a descriptive type. Research data were obtained from observations and documentation from film observations that were considered to have a da'wah message. This research resulted in the meaning and message of the da'wah film Ustadz Millennial. First, the meaning of the Denotation in this film is about Ahmad's daily expression in treating parents, relatives, and friends. The meaning connotations are to fix intentions only to God, learning not limited to time and place, filial piety to parents, the sin of fellowship with jinns, discussing problems together, civility to parents, and an attitude of tolerance. The myth in this film about applying principles based on religion in everyday life makes life always intended for Allah, and morals are maintained and ordered. The message of da'wah in the film Ustadz Milenial is identified in 3 subjects of da'wah messages such as Akidah on faith in Allah, Sharia about the commandments and laws of God, one of which is the command to be respectful to parents, Morals, civility, deliberation, friendship, and tolerance.